Morphometric features of the venous vasculature in spleen as a fractal system - A. Sh. Dadashev; I. S. Miltykh; O. K. Zenin; E. S. Kafarov (Сибирский научный медицинский журнал, 2024)
The aim of the study is to determine the morphometric features of splenic vasculature structural components (biounits, BU) of various kinds in individuals of different sex and age. Material and methods. The paper is based on the results of morphometric study of corrosion casts of splenic venous vasculature of 64 people (32 men, 32 women) at the age of 21 to 60 years (32 first period of adulthood, 32 second period of adulthood), deceased from sudden death and accidental causes. The study was conducted in compliance with ethical principles, including the World Medical Association’s Declaration of Helsinki. The diameters (D) and lengths (L) of the venous segments constituting BU were measured. Splenic venous vasculature was represented as a system consisting of three types of BU: 1 BU – the proximal segment diameter (D) is less than the sum of the diameters of distal segments (dmax and dmin) associated with it, D < dmax + dmin; 0 BU – D = dmax + dmin; 2 BU – D > dmax + dmin. Results. All three kinds of BUs were identified; there was a significant relationship between the relative number of BUs of different kinds, sex and age group; the sizes of all three kinds of BUs were determined; 1 BU was the largest and 0 BU was the smallest; 0 BU was the most symmetrical and 2 BU was the most asymmetrical; the relative number of 1 BU decreased, 0 BU increased, and 2 BU practically did not change in the direction from proximal to distal parts of the channel. BUs of the 1st kind have the largest diameter of proximal segments, while 2 BUs occupy the middle position in the range of values of the investigated parameters. The smallest diameter belongs to 0 BU. As for the length of segments L, the maximum values are typical for 1 BU, the minimum – for 2 BU, and the middle position in the series is occupied by 0 BU. Conclusions. The results obtained can serve as a foundation for the creation of a morphometric standard of splenic venous vasculature, and should be considered in its numerical modelling.